PREVALENCE AND RISK PREDICTORS OF POST OPERATIVE ATRIAL FIBRILLATION AFTER HEART SURGERY UNDER CPB - ZAFAR, H; AHMED, N; AJMAL, N (Biological and Clinical Sciences Research Journal, 2022)
The current analysis was designed to assess the prevalence and risk predictors of atrial fibrillation after heart surgery performed under cardiopulmonary bypass (CPB). A descriptive observational study was conducted in the Cardiology Department of Faisalabad Cardiology Hospital, Faisalabad. A total of 150 patients older than 18 years old undergoing CABG and valvular surgery performed by cardiopulmonary bypass were included in the study. The association of POAF and risk factors, including age, LVEF<40%, history of diabetes, myocardial infarction, beta-blocker therapy, COPD, aortic cross-clamp time, CPB time, inotropic, and ventilation support, was evaluated. The patients with no history of beta blockers showed less risk of developing AF (OR: 0.153); hence the use of beta-blockers is significantly associated with AF. Similarly, patients with LVEF less than 40% and inotropic support for 30 minutes also had less odds of AF (0.174, 0.127); hence these variables are also significantly associated with AF. A history of myocardial infarction increased the risk of AF to 6.27 times. Using a ventilator for> 24 hours increased the incidence of AF to 12.28 times. LVEF <40%, inotropic and ventilation support, myocardial infarction, and CPB time preoperatively are strong predictors of POAF after cardiac surgery.